THEORETICAL ASPECTS OF FORMATION OF SOCIO-PROFESSIONAL SELF-DETERMINATION OF LEARNERS AT EDUCATION ESTABLISHMENTS - Alla Ya. Zhurkina; Evgeny G. Sergushin; Olga V. Sergushina (National Research Mordova State University, 2016)
Introduction: the article reveals the theoretical aspects in formation of socio-professional self-determination of learners in education institutions. The emphasis is on interdisciplinary links, integration approaches in the study of problems of self-determination. Materials and Methods: the article was written using a number of methods of theoretical pedagogical study, allowing mental penetration into the essence of the phenomenon under study teacher: analysis, synthesis, comparison, generalization method of investigating causal relationships. Results: the authors reveal the essence of the socio-professional self-determination and present grounds for separation of this concept out from the pyramid of the terms that characterise the description of the career choice process. The article substantiates the social orientation of the act of choosing a profession. It argues that career choice affects the future social position. Knowledge of theoretical bases of process of socioprofessional self-determination is very important for preparation of children for conscious career choices. Special attention is paid to the regularities, principles and f actors of this process. Discussion and Conclusions: giving a thorough account of internal and external factors of socio-professional self-determination, the authors propose to consider them solely in the system, with its inherent dynamics and the inextricable connection with the environment, suggest that changes in the social environment always entail changes in the system of factors. The article is concerned with the problem of contradictions of the process of formation of socio-professional self-determination. The authors highlight the leading role of pedagogical support in the process of socio-professional self-determination of a student's personality, analyse modern approaches to the concept of pedagogical support. The authors characterize the educational support system as a professional educator focused on creating social and pedagogical conditions for the successful training, education and development learner in the educational process. According to the authors, for the effective development of socio-professional self-determination of students one should focus on compliance with the principles, accounting regularities and factors of this activit y.